Microstrip spiral resonator for the UWB chipless RFID tag - Hossain, A. K. M. Z.; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (Springer International Publishing, 2015)
A resonator type chipless RFID tag comprised of two separate antennas, one transmission line with spiral resonators. The key element of a chipless RFID tag is its passive spiral microstrip resonator circuit which contains the data bits for the tag. To decrease the dimension of resonator in chipless tag is still challenging task. At present rectangular spiral shaped resonator is used in the chipless tag for UWB RFID system. A circular spiral microstrip resonator design is proposed for space reduction in the chipless RFID tag. A comparison has been made between rectangular and circular shaped spiral resonators for 2.5 GHz frequency using CST MWS. The result shows a reduction in area of 9.8 % has been achieved by a microstrip circular spiral resonator